Tests and characterization of a laterally graded multilayer Montel mirror. (1st January 2014) - Mundboth, K.; Sutter, J.; Laundy, D.; Collins, S.; Stoupin, S.; Shvyd'ko, Y.
<x xml:space="preserve">Abstract</x> Multilayers are becoming an increasingly important tool in X‐ray optics. The essential parameters to design a pair of laterally graded multilayer mirrors arranged in a Montel‐type configuration for use as an X‐ray collimating device are provided. The results of X‐ray reflectometry tests carried out on the optics in addition to metrology characterization are also shown. Finally, using experimental data and combined with X‐ray tracing simulations it is demonstrated that the mirror meets all stringent specifications as required for a novel ultra‐high‐resolution inelastic X‐ray scattering spectrometer at the Advanced Photon Source.